ANALYSIS OF ROBUSTA COFFEE PRODUCT PACKAGING QUALITY CONTROL USING STATISTICAL PROCESS CONTROL (SPC) METHOD APPROACH - sobron (Journal Knowledge Industrial Engineering (JKIE), 2023)
UD.Kopi Lesung is engaged in producing coffee, including robusta and arabica coffee with roastbean and greenbean processes with various processing ranging from organic to full wash. The focus of the research is to reduce defects in roastbeen coffee product packaging, so it is necessary to plan control efforts. One way that can be taken is to implement statistical quality control. Based on control, control limits are determined for each product defect. From the analysis of the control chart, on average there are still deviations in coffee packaging defects, namely the position of the sealer is not right, the grammage is not right, the plastic roll does not match the machine. From the fishbone diagram, the cause of the problem can be identified, namely: operator error in controlling the coffee packaging work process, because the influence of the age of the machine and supporting equipment causes a decrease in productivity for the quality of the packaging produced. With this method, a plan is obtained to overcome the problem of defects that occur, namely the company must carry out periodic maintenance on the machine, pay attention to the condition of the operator while working, and strictly select the materials received from suppliers. This mitigation is expected to improve quality control in the company.